The urbanization of summer holiday estates surrounding Łódź: Wiśniowa Góra - Matczak, Andrzej (Turyzm/Tourism, 2009)
The article presents the reconstruction of the urbanization process in Wiśniowa Góra, a village near Łódź. It came into being in 1870 as a farming village, surrounded by a forest. After several years the holiday function developed there, which became the base for the general development of the destination during the inter-war period. In 1945 - 1989 Wiśniowa Góra became a dormitory village and a summer holiday estate. The political and economic transformation, which started in 1989, has led to the collapse of the holiday function and the development of the residential function, thus transforming Wiśniowa Góra into a Łódź suburb.